2022
DOI: 10.3390/medicina58070877
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Adherence and Antimicrobial Activities of Silver Nanoparticles against Serotypes C and K of Streptococcus mutans on Orthodontic Appliances

Abstract: Background and Objectives: Streptococcus mutans (S. mutans) is the main microorganism associated with the presence of dental caries and specific serotypes of this bacteria have been related to several systemic diseases limiting general health. In orthodontics, white spot lesions (WSL), represent a great challenge for clinicians due to the great fluctuation of their prevalence and incidence during conventional orthodontic treatments. Although silver nanoparticles (AgNP) have been demonstrated to have great anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…In the study by Espinosa-Cristóbal et al, Ag NPs exhibited greater antimicrobial effects on S. mutans at lower concentrations than gold or zinc [ 2 ]. In a study by Valodkar et al, Ag-Cu NPs showed antimicrobial effects on gram-positive and gram-negative bacteria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Espinosa-Cristóbal et al, Ag NPs exhibited greater antimicrobial effects on S. mutans at lower concentrations than gold or zinc [ 2 ]. In a study by Valodkar et al, Ag-Cu NPs showed antimicrobial effects on gram-positive and gram-negative bacteria [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization's Global Oral Health Status Report for the year 2022, oral diseases have a significant impact on approximately 3.5 billion people worldwide, with approximately 75% of those affected residing in middle-income countries both in developed and economically disadvantaged countries, dental caries remain a significant public health concern [ 1 ]. Following the identification of Streptococcus mutans ( S. mutans ) as the causative agent of dental caries, considerable attention has been directed towards targeting this bacterium in disease prevention efforts through the use of antimicrobial agents and vaccine development [ 2 ]. In conclusion, there is a need for a substance that does not promote bacterial resistance and exhibits strong bactericidal properties.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, silver nanoparticles (AgNP) have exhibited significant antibacterial activity against cariogenic bacteria ( Sánchez-Tito and Tay, 2021 , Yassaei et al, 2020 ). Additionally, the anti-adherence properties of AgNP have been tested, and they are effective in inhibiting the adhesion of S. mutans on the surface of orthodontic materials ( Nafarrate-Valdez, et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs are heavily utilized in research settings for their antimicrobial properties and have demonstrated promising results even against resistant bacterial strains [ 7 , 8 , 9 , 10 ]. AgNPs offer numerous advantages as antimicrobial agents in terms of their adherence and penetration ability toward the cell surface of bacteria [ 11 , 12 , 13 ]. In addition, AgNPs that are stabilized by chitosan (CS) provide avenues for complexation with biological molecules, such as deoxyribonucleic acid (DNA) and ribonucleic acid (RNA), via their phosphorus and sulfur donor ligands [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%